Expression of novel amylases in Saccharomyces cerevisiae for the efficient conversion of raw starch to bioethanol - Cripwell, Rosemary Anne (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.